Trust mechanisms : an integrated approach for e - commerce website development process - Akmal Rakhmadi, author; Nur Zailan Othman, author; Ab. Razak Che Hussin, author; International Symposium on Information Technology (2008: Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL